Austria : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses key findings of the Detailed Assessment of Basel Core Principles for Effective Banking Supervision on Austria. Since the outbreak of the financial crisis, some Austrian credit institutions had to be nationalized as an ad hoc measure to prevent contagion effects and to preserve financial stability. Bank capital ratios are improving but still lag behind other internationally active banks. Bank profits have been affected by low net interest income and risk provisioning reflecting higher nonperforming loans ratios. Austrian banks' funding structure is relatively stable, and financing conditions have improved since the peak of the crisis.